2014
DOI: 10.1371/journal.pone.0099171
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neurodegeneration and Cognitive Impairment in Neonatal Mice Exposed to Propofol or Isoflurane

Abstract: BackgroundWhile previous studies have demonstrated neuronal apoptosis and associated cognitive impairment after isoflurane or propofol exposure in neonatal rodents, the effects of these two anesthetics have not been directly compared. Here, we compare and contrast the effectiveness of isoflurane and propofol to cause neurodegeneration in the developing brain and associated cognitive dysfunction.MethodsSeven-day-old mice were used. Mice in the isoflurane treatment group received 6 h of 1.5% isoflurane, while mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 60 publications
2
53
2
Order By: Relevance
“…Neuronal apoptosis or synaptic loss induced by general anesthetics have been reported in the previous studies, but the results were from only one time point after propofol exposure, such as at P14 or P21 (Yu et al, 2013;Yang et al, 2014;Lunardi et al, 2010;Amrock et al, 2015), and the relationship between neuronal apoptosis or synapse formation and cognitive impairment induced by propofol is inaccurate. The present study demonstrates that multiple exposures to propofol at early age induce persistent neuronal apoptosis, neuronal deficit, synaptic loss and long-term cognitive impairment; while single exposure to propofol only induces transient neuronal apoptosis and deficit.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Neuronal apoptosis or synaptic loss induced by general anesthetics have been reported in the previous studies, but the results were from only one time point after propofol exposure, such as at P14 or P21 (Yu et al, 2013;Yang et al, 2014;Lunardi et al, 2010;Amrock et al, 2015), and the relationship between neuronal apoptosis or synapse formation and cognitive impairment induced by propofol is inaccurate. The present study demonstrates that multiple exposures to propofol at early age induce persistent neuronal apoptosis, neuronal deficit, synaptic loss and long-term cognitive impairment; while single exposure to propofol only induces transient neuronal apoptosis and deficit.…”
Section: Discussionmentioning
confidence: 90%
“…It has been confirmed that the developing brain is susceptible to anesthetic-induced neuronal apoptosis at the peak of synaptogenesis, and the greatest vulnerability in rodents occurs predominantly from postnatal day (P) 7 to P10 (Yon et al, 2005;Rizzi et al, 2010), it was considered that anesthetic-induced acute neuronal apoptosis may be a critical contributing factor to long-term cognitive and behavioral impairment, but recent studies have demonstrated that anesthetic-induced acute neuronal apoptosis does not cause long-term cognitive impairment (Yang et al, 2014;Loepke et al, 2009). Therefore, the role of neu-ronal apoptosis in long-term cognitive impairment needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In newborn mice, general anaesthesia with 1.5 Vol.% isoflurane has been found to cause a 4-11 fold increase of neuronal death in various brain regions, as compared to controls. [10,28,29] A 6-hour isoflurane exposure eliminates approximately 2% of cortical neurons [14]. Apoptosis appears to be the predominant mode of isoflurane-induced death, as evidenced by caspase-3 cleavage [10].…”
Section: Resultsmentioning
confidence: 99%
“…Several anesthetics, including ketamine, midazolam, isoflurane, and propofol, have been reported to cause neurodegeneration in the developing brain and subsequent cognitive dysfunction in several animal models [2][3][4][5][6][7]10]. Propofol has also been reported to cause neuroapoptosis in the developing brain at clinically relevant concentrations and durations, leading to neurocognitive dysfunction [24,25]. In terms of the impact of propofol on long-term cellular and neurocognitive functions in neonatal mice, we found vigorous cell loss and hindered cognitive performance in propofol-treated mice in adulthood compared to controls.…”
Section: Discussionmentioning
confidence: 99%